The Black Flies (Diptera: Simuliidae) of Iran - Khazeni, Atefeh; Adler, Peter H.; Telmadareiiy, Zakieh; Oshaghi, Mohammad Ali; Vatandoost, Hasan; Abtahi, Seyed Mohammad; Lotfi, Abolfazl (Zootaxa, 2013)
Although Iran has a large geographic area encompassing 13 ecoregions, its simuliid fauna remains largely unexplored. To begin redressing this faunal gap, we reviewed literature records and coupled morphological and chromosomal identifications of material newly collected from 16 sites in Iran. Twenty-three nominal species are now recognized, including new country records for Simulium crassicaulum (Rubtsov) and Simulium alajense Rubtsov, and the southernmost world record for Simulium transcaspicum Enderlein. Multiple cytoforms of the Simulium aureum group, Simulium bezzii complex, and Simulium ornatum group were found.